A step towards improving workflow practices for volume crime investigations: outcomes of a 90-day trial in South Australia. - Brown, Cheryl M.; Clark, Yvette; Julian, Roberta; Kelty, Sally (Police Practice & Research, 2018)
The provision of forensic science services in volume crime investigations works most successfully as a partnership between police agencies and external forensic laboratories as opposed to a client/provider model where unlimited demand ignores finite resources. The principles of Lean Six Sigma have been applied in various laboratories to improve workflow through identification of wasteful work practices. These strategies are aimed at process optimisation through the application of triaging, a concept that has rarely been studied yet referenced strongly in the literature. The South Australia End to End 90-Day Trial: facilitating quicker justice through timely evidence processing, is a collaborative approach between South Australia Police and Forensic Science South Australia. This trial applied evidence-based policing principles, a law enforcement philosophy that uses research undertaken with scientific processes to inform law-enforcement decision-making. The results demonstrate how a review of processes and the removal of non-value adding activities can improve service delivery while not exhausting those ‘finite resources’.